Expression of Locality in Text Syntax - Zokirov Muxtorali Turdaliyevich (Zien Journals, 2023)
In this article, the issues of expressing the philosophical categories of space and time at the syntactic level of the language are covered. Theoretical observations are proved on the basis of examples taken from the works of Isojon Sultan, one of the famous representatives of modern Uzbek literature.
Keywords: linguistics; text; syntax; conjunction